The Fragile Success of Team Start-ups - Erik Stam; Veronique Schutjens (Max Planck Institute for Research into Economic Systems, 2005)
This article describes the benefits and pitfalls of starting a firm with an entrepreneurial team, drawing on a longitudinal empirical analysis of the life course of 90 team start-ups and 1196 solo start-ups in the Netherlands. In the first three years of their existence, team start-ups perform better than solo start-ups on several success indicators. However, after this start phase, entrepreneurial teams face particular problems in realizing further growth. These team-specific bottlenecks can even threaten firm survival. In later life course phases we found a clear distinction between entrepreneurial teams with stagnating growth and teams that succeeded in solving these problems and went on to realize further growth.
Keywords: M13; L25; D92; D74; D23; D21; M54; 330; entrepreneurial teams; start-ups; firm growth; life course analysis; Unternehmensgründung; Unternehmer; Gruppenarbeit; Unternehmensentwicklung; Niederlande